A study on factors influencing young and matured adult learners to continue their education / Kaussalya Verasingam ...[et al.] - Verasingam, Kaussalya; Supramaniam, Kaarthiyainy; Arumugam, Nalini; Sathyiasenan, Sai Dharinee (Universiti Teknologi MARA Shah Alam, 2020)
Distance learning is one convenient form of education for adult learners who aspire to advance their career as well as to meet the demand at workplace. Thus, this study aims to investigate factors encouraging adult learners to continue their education and their coping strategies with challenges they encounter as adult learners. This group of adult learners furthers their studies through a distance learning programme via a system called 'ilearn', which is offered by the institution. This study adopted quantitative methodology to elicit information and substantiated with structured interview responses to add credibility to the findings. Eighty-two adult learners from Bachelor of Finance, UiTM Shah Alam participated in this study. The results indicated that the main factors motivating adult learners to pursue their education are their aspiration for professional advancement, monetary gains and improving their quality of lifestyle. The results also revealed that financial constraints and time factor are the most significant barriers affecting adult learners' mindset and they strive to overcome these challenges by approaching banks for study loans and opting out for distance learning programme offered during weekends. These two options reduce their hurdles slightly and they are able to cope with their choice of furthering their education.